85.0k views
5 votes
2 - 4 ( y + 4 ) = 2y + 16 solve for y

User Rwyland
by
5.4k points

1 Answer

1 vote

Answer:

y = -5

Explanation:

To solve for a variable, take the following steps:

  • Distribute by multiplying into each term in the parenthesis
  • Combine like terms
  • Move terms across the equal sign using inverse operations

2 - 4 (y + 4) = 2y + 16 Distribute

2 - 4y - 16 = 2y + 16 Combine 2-16

-14 - 4y = 2y + 16 Add 4y to both sides

-14 = 6y + 16 Subtract 16 to both sides

-30 = 6y Divide by 6

y = -5

User Stefan Meyer
by
5.2k points